Present Status of Marine Radioecology in Jakarta Bay - H. Suseno; B Budiawan; M Muslim; M. Makmur; M. N. Yahya (Atom Indonesia, 2018)
Operation of nuclear facilities such as research reactor and it’s supporting installation in Serpong Nuclear Area may release controlled  radionuclides to Cisadane River and then it would flow to Jakarta Bay. There are limited marine radioecology studies or radionuclides monitoring  at Jakarta Bay. Therefore monitoring of 239/240Pu and 137Cs was carried out from Tanjung Pasir to Tanjung Kerawang. The ERICA Assessment Tool was used to evaluate radiological risk in the marine environment of Jakarta Bay area. The 137Cs concentration in sea water and sea sediments were in range of  0.17 – 1.17 Bq.m-3 and  0.34 – 1.21 Bq.kg-1, respectively. Moreover,  result of 239/240Pu measurement showed that concentration at sea water and sea sediment were range from < MDA – 0.53 mBq.m-3 and 2.64 – 55.70 mBq.kg-1 respectively. The results of risk analysis were indicated that all the total dose rates per organism were millions time lower than the screening    rate (10 mGy.h-1).